The aggregate production function and the measurement of technical change 'not even wrong' - Felipe, Jesus ca. 20./21. Jh; McCombie, John S. L. 1950- (Edward Elgar, 2013)
'This is an extremely important and long-awaited book. The authors provide a cogent guide to all that is wrong with the theory and empirical applications of the discredited notion of an aggregate production function. Their critique has devastating implications for orthodox macroeconomics.' (Anwar Shaikh, New School for Social Research, US). --
Keywords: Wirtschaftstheorie; Produktionsfunktion; Produktionsfunktion / (DE-627)091384478 / (DE-STW)10327-4; Technischer Fortschritt / (DE-627)091394236 / (DE-STW)10466-4; Messung / (DE-627)091377455 / (DE-STW)19033-4